2008
DOI: 10.1111/j.1439-0523.2008.01505.x
|View full text |Cite
|
Sign up to set email alerts
|

A genetic linkage map of Physocarpus, a member of the Spiraeoideae (Rosaceae), based on RAPD, AFLP, RGA, SSR and gene specific markers

Abstract: Physocarpus opulifolius is a deciduous shrub native to North America belonging to the Spiraeoideae subfamily of the Rosaceae. The cultivars ÔLuteusÕ and ÔDiaboloÕ are grown in gardens for their ornamental foliage, golden and purple respectively. We developed a linkage map of P. opulifolius with a view to detecting markers for the leaf colour genes, which are under major gene control. A total of 162 molecular markers (128 RAPDs, 27 AFLPs, three RGA, three STS markers and one SSR) and the leaf colour genes Pur a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The resulting seedlings segregated for purple and green foliage and were generally intermediate in growth habit. Segregation of purple vs. green leaves in this population is consistent with the finding of Sutherland et al (2008) that 'Monlo' is heterozygous for Pur. Genotypes from this population with purple foliage and mildew resistance were retained as parents.…”
Section: Originsupporting
confidence: 88%
See 2 more Smart Citations
“…The resulting seedlings segregated for purple and green foliage and were generally intermediate in growth habit. Segregation of purple vs. green leaves in this population is consistent with the finding of Sutherland et al (2008) that 'Monlo' is heterozygous for Pur. Genotypes from this population with purple foliage and mildew resistance were retained as parents.…”
Section: Originsupporting
confidence: 88%
“…Leaf color segregation data from progeny of 'Donna May' are consistent with 'Donna May' being heterozygous for the Pur gene as would be expected from its pedigree. 'Donna May' and its compact purple-leafed siblings were allowed to intermate in isolation in 2007 (ninebark is self-incompatible; Sutherland et al, 2008). The segregation data for purple vs. green offspring from the bulked seed collected off of these plants fit the expected 3:1 ratio for offspring from parents heterozygous for Pur (Table 2).…”
Section: Description and Performancementioning
confidence: 78%
See 1 more Smart Citation
“…The ornamental genus Physocarpus (Nelliaea 2 n = 2 x = 18) in the Spiraeoideae was positioned as an immediate sister genus to Prunus in a comprehensive phylogeny of the Rosaceae [ 1 ]. A molecular map, based on a segregating F 2 progeny was reported for the species, which spanned the expected nine linkage groups and contained a total of 181 molecular markers across 586.1 cM, along with two genes controlling leaf colour [ 9 ]. Although the authors reported the positions of three sequence-characterised gene-specific markers and a single Malus SSR marker, the remaining 177 markers were either AFLP or RAPD markers and thus were not readily applicable to comparative genomic studies with other Rosaceous genera.…”
Section: Introductionmentioning
confidence: 99%
“…In this investigation, we have elaborated the previously published genetic linkage map of Physocarpus [ 9 ] using SNP markers identified through GBS. We used this map to study the extent of the genome diversification between the Physocarpus genus, with a base chromosome number of x = 9 and Prunus , x = 8, its phylogenetically close relation for which a full genome sequence is available.…”
Section: Introductionmentioning
confidence: 99%